Manajemen Strategi Dakwah Radio Di Era Digital - Bambang Agus Setiyawan; Umi Halwati (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Sekolah Tinggi Agama Islam Mulia Astuti (STAIMAS) Wonogiri, 2022)
The rapid development of information technology has caused changes in the order of various sectors of life, including in the world of radio broadcasting. This, if not addressed properly, can be fatal with the abandonment of the media by his fans and moving on to others. Radio Insani Purbalingga, which in its broadcast focuses on Islamic dawah, must adapt by implementing management and strategies in dealing with these conditions. This research uses a qualitative approach using the concept of POAC (Planning, Organizing, Actuating, Controlling). In the management and strategy, Radio Insani Purbalingga prepares the program of the event, selects and sorts the speakers, and places the event at the right time so that it is more attractive to the audience. In addition, Insani FM radio also uses online channels as support and expands its reach to the audience. The conclusion of this study is that Radio Insani Purbalingga is able to carry out its management and strategy well so that it can maintain its existence as a da'wah radio in the digital era.